Production and applications of lead (II) oxide/poly(aniline-co-thiophene) composite materials for enhanced supercapacitor performance - Hacinecipoglu, Ayse V.; Efeoglu, Selen; Kir, Burak; Balik, Berk; Gencten, Metin (SPRINGER, 2024)
In this work, a novel approach was employed to prepare and utilize lead (II) oxide and poly(aniline-co-thiophene) (PANI-co-PTh) composite materials as electrode materials for supercapacitors, marking the first instance of such utilization in the literature. PANI-co-PTh was synthesized in bulk through chemical polymerization, and the conducting polymers underwent comprehensive spectroscopic, physical, and microscopic characterization. Subsequently, the material, incorporating lead (II) oxide (PbO) as a composite, was employed as electrode materials in asymmetric-type supercapacitors. The main results indicate a clear relationship between the surface area of conducting polymers and their specific capacitance. Notably, PANI-co-PTh-6, possessing the highest surface area, demonstrated the highest specific capacitance. Particle size distribution and specific surface area for PANI-co-PTh-6 were determined as 130 mu m and 64.76 m2g-1, respectively. The PbO@PANI-co-PTh-3 configuration exhibited the highest specific capacitance, reaching 294 Fg-1 at a 10 mVs-1 scan rate. Remarkably, during long-cycle experiments, this system demonstrated a capacity retention of 70.69% after 1000 cycles. The inaugural application of the PbO@PANI-co-PTh-3 supercapacitor showcased notable capacitance values, establishing a substantial foundation for future research endeavors in this field.
Keywords: CONDUCTING POLYMERS; METAL-OXIDES; ELECTRODE MATERIALS; POLYTHIOPHENE; THIOPHENE; COPOLYMER; NANOCOMPOSITE; NANOPARTICLES; POLYANILINE; HYBRIDS; Engineering; Materials Science; Physics